2012
DOI: 10.1177/0146621612469825
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the Item Parameter Estimates and Robust Automated Test Assembly

Abstract: 2 AbstractIRT parameters have to be estimated, and because of the estimation process, they do have uncertainty in them. In most large scale testing programs, the parameters are stored in item banks, and automated test assembly algorithms are applied to assemble operational test forms. These algorithms treat item parameters as fixed values, and uncertainty is not taken into account. As a consequence, resulting tests might be off target or less informative than expected. In this paper, the process of parameter e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In previous papers about robust test assembly (De Jong et al, 2009;Veldkamp, 2013;Veldkamp et al, 2013), uncertainty in test assembly was always related to uncertainty in the item parameter estimates. In this article, uncertainty was related to the violation of the assumption of LI, and the presence of testlet effects in TRT models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous papers about robust test assembly (De Jong et al, 2009;Veldkamp, 2013;Veldkamp et al, 2013), uncertainty in test assembly was always related to uncertainty in the item parameter estimates. In this article, uncertainty was related to the violation of the assumption of LI, and the presence of testlet effects in TRT models.…”
Section: Resultsmentioning
confidence: 99%
“…A less conservative alternative was proposed in De Jong et al (2009), where only 1 SD was subtracted. Veldkamp et al (2013) studied the De Jong et al (2009) method more into detail and found that subtracting 1 SD for all items might not be realistic and for long tests it might be too conservative. Soyster (1973) based methods assume all the uncertain coefficients parameters have maximum impact on the solution of a 0-1 LP problem, which is usually not the case in practice.…”
Section: Robust Ata With Testletsmentioning
confidence: 99%
“…Often this parallelism is pursued by minimizing the maximum distance with respect to a specific statistical target of the reference test form, using what is called a Minimax MILP model (van der Linden, ). Commonly only the TIF (Swanson & Stocking, ; van der Linden & Adema, ; Veldkamp, Matteucci, & de Jong, ), or on some occasions only the TCC (Armstrong, Jones, & Kunce, ; Armstrong et al., ) are used as statistical targets. However, both statistical targets can be combined in one Minimax model (Ali & van Rijn, ).…”
Section: Discussionmentioning
confidence: 99%
“…But instead of using the infima of these distributions, they subtracted one posterior standard deviation from the estimated Fisher information as a robust alternative. This approach was even studied more into detail by Veldkamp et al (2013), who studied the effects of uncertainties in various item parameters on Fisher information in the assembly of linear test forms.…”
Section: Robust Test Assemblymentioning
confidence: 99%